2016
DOI: 10.1002/stem.2536
|View full text |Cite
|
Sign up to set email alerts
|

p27kip1 Is Required for Functionally Relevant Adult Hippocampal Neurogenesis in Mice

Abstract: We asked whether cell-cycle associated protein p27kip1 might be involved in the transition of precursor cells to postmitotic maturation in adult hippocampal neurogenesis. p27kip1 was expressed throughout the dentate gyrus with a strong nuclear expression in early postmitotic, calretinin-positive neurons and neuronally determined progenitor cells (type-3 and some type2b), lower or absent expression in radial glia-like precursor cells (type-1) and type-2a cells and essentially no expression in granule cells. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Acquisition learning may be less sensitive than reversal learning to modulation of hippocampal neurogenesis, as suggested by previous studies demonstrating that an attenuation of adult neurogenesis does not prevent acquisition of the escape platform location during water maze training [20,96]. Brain-injured WT and brain-injured IGF overexpressing mice showed equivalent abilities to learn the location of a hidden platform during the acquisition phase (days 1-2) of RAWM testing.…”
Section: Reversal Learningmentioning
confidence: 87%
“…Acquisition learning may be less sensitive than reversal learning to modulation of hippocampal neurogenesis, as suggested by previous studies demonstrating that an attenuation of adult neurogenesis does not prevent acquisition of the escape platform location during water maze training [20,96]. Brain-injured WT and brain-injured IGF overexpressing mice showed equivalent abilities to learn the location of a hidden platform during the acquisition phase (days 1-2) of RAWM testing.…”
Section: Reversal Learningmentioning
confidence: 87%
“…Detailed immunophenotyping revealed that p27 kip1 is expressed by virtually all type 1 NSCs, in the majority of IPCs, in neuroblasts and immature neurons (Qiu et al, 2009; Andreu et al, 2015). Deletion of p27 kip1 increases proliferation of radial aNSC in vivo and in vitro , and Ki67 can be detected only in those few aNSCs that are p27 kip1 -negative, demonstrating a role of p27 kip1 in aNSC quiescence (Qiu et al, 2009; Andreu et al, 2015; Horster et al, 2017). Activation of p27 kip1 mutant NSCs has no effect on the total size of the aNSC pool, indicating that p27 kip1 has no role in the choice between symmetric and asymmetric aNSC divisions (Andreu et al, 2015).…”
Section: Specific Roles Of Cell Cycle Components In Regulating Adult mentioning
confidence: 99%
“…Recent studies also provided some insight into the role of p27 kip1 in differentiation. P27 kip1 increases upon neuronal differentiation in vitro and in vivo (Varodayan et al, 2009; Andreu et al, 2015; Horster et al, 2017). It becomes induced by proneural genes, such as NeuroD2 or Mash1, suggesting that p27 kip1 is employed by neural determination factors to force differentiation and CC exit (Farah et al, 2000).…”
Section: Specific Roles Of Cell Cycle Components In Regulating Adult mentioning
confidence: 99%
“…Consequently, p19/p27 double KO mice showed an abnormal mitotic activity in post-migratory neurons, resulting in a phenotype characterized by bradykinesia, proprioceptive abnormalities, muscle weakness, seizure and death occurring after few weeks from birth, probably because of their inability to feed themselves [30]. More recently, Kempermann et al reported that mice employed in behavioral activities displayed an upregulation of cytoplasmic p27 in the neurogenic zone of the hippocampus, which is devoted to integrating established memory with new pieces of information, suggesting that p27 could also play a role in post-mitotic neurons [31]. Indeed, it is to note that p27 KO mice display a “neurogenesis phenotype” characterized by impaired spatial learning ability if challenged with specific trials requiring hippocampus-dependent strategies [31].…”
Section: Main Textmentioning
confidence: 99%
“…More recently, Kempermann et al reported that mice employed in behavioral activities displayed an upregulation of cytoplasmic p27 in the neurogenic zone of the hippocampus, which is devoted to integrating established memory with new pieces of information, suggesting that p27 could also play a role in post-mitotic neurons [31]. Indeed, it is to note that p27 KO mice display a “neurogenesis phenotype” characterized by impaired spatial learning ability if challenged with specific trials requiring hippocampus-dependent strategies [31]. Although this phenotype seems to be linked to a cytoplasmic localization of p27, it has not been clearly linked to alterations of the cytoskeleton dynamics.…”
Section: Main Textmentioning
confidence: 99%